Digital multilocality: New modes of working between center and periphery in Switzerland. (December 2021) - Bürgin, Reto; Mayer, Heike; Kashev, Alexander; Haug, Sigve
Abstract: The use of information and communication technologies (ICTs) allows to work in multiple locations. The purpose of this article is to investigate how multilocal knowledge workers engage in work in the interplay of workplaces between cities and mountain regions. We follow a mixed methods approach with intertwined quantitative and qualitative data sources. The results show that working in the periphery using marginality can be beneficial and disadvantageous at the same time. Furthermore, marginality is seldom utilized for creativity but preferably for working undisturbed. This study contributes to the literature on marginality and flexible working between urban centers and rural peripheries in the digital age. Highlights: Multilocal knowledge workers strategically seek to work in peripheries. Mixed methods approach identifies subtleties of work at different locations. Using marginality for work is beneficial and disadvantageous at the same time. Cyclical working in center and periphery increases work efficiency. Localization of creative activities must be reconsidered due to multilocal work.